Resveratrol-derived carbon dots integrated into gelatin/chitosan multifunctional films for intelligent packaging - Tianxin Fu; Yuchao Feng; Shu Zhang; Yanan Sheng; Changyuan Wang (Food Chemistry: X)
In this study, multifunctional Resveratrol-derived carbon dots (Res-CDs) were prepared using a hydrothermal method. Res-CDs exhibited good free-radical scavenging activities, attributed to abundant surface hydroxyl groups, and effectively inhibited Staphylococcus aureus and Escherichia coli growth at a concentration of 2 mg/mL. Composite films were prepared by combining Res-CDs with gelatin/chitosan. As well as excellent mechanical properties, the prepared films exhibited smooth surfaces, thermal stability, and good antioxidant, ultraviolet-shielding, antibacterial, and pH-responsive properties. Furthermore, cell viability measurements showed that the films were safe. When applied to keeping pork fresh, the gelatin/chitosan/Res-CDs film significantly reduced the total viable bacterial count on the pork surface and effectively prevented pork discoloration. Additionally, pH, total volatile basic nitrogen, and weight loss measurements confirmed the preservative effects of the film on pork. This work provides a new approach for synthesizing bionanocomposite films with applicability in the food industry.